Migratory connectivity of barn swallows in South Africa to their Palaearctic breeding grounds. Issue 11 (6th July 2018) - Burman, Marc S.; Underhill, Leslie G.; Altwegg, Res; Erni, Birgit; Remisiewicz, Magdalena; MacLeod, Jack
Abstract: Aim: To demonstrate that the population of barn swallow Hirundo rustica in South Africa in the austral summer is not a pan‐mixture of birds from their vast Palaearctic breeding range and to estimate proportions of barn swallows in four South African regions migrating to three breeding ground zones. Location: South Africa and Eurasia. Methods: We analysed citizen science barn swallow ringing records, obtained between 1954 and 2011 in South Africa, and their recoveries made in Eurasia. We used the "division coefficient" method to model the spatial variability of the recovery process and to estimate proportions of barn swallows ringed in four regions of South Africa (KwaZulu‐Natal, Gauteng, eastern part of Northern Cape and the Western Cape) migrating to three zones in the Eurasian breeding grounds: western (west of 10°E), central (10°–60°E) and eastern (east of 60°E). Results: The percentages of barn swallows migrating from KwaZulu‐Natal to the eastern and central Palaearctic zones were estimated at 54.0% and 46.0%, respectively. The percentages from Gauteng to the central and western zones were 80.5% and 15.7%, from the Northern Cape to the central and western zones were 43.7% and 56.3% and from the Western Cape to the eastern, central and western zones were 30.8%, 35.4%, 33.8%. The estimate of the observer process suggested that reencounter rates per 10, 000 swallows ringed increased from east to west: 32 reencounters per 10, 000 in the eastern zone, 36 in the central zone and 50 in the western zone. Main conclusions: These results provide the first quantitative estimates of the composition of barn swallow populations in four regions of South Africa, relative to their Palaearctic breeding zones.